Correction: Drought resistance of Argania spinosa L. colonized by the arbuscular mycorrhizal fungus Rhizophagus irregularis varies according to accession - , Frontiers Production Office (Frontiers in Plant Science, 2025)
Graphical AbstractDiagram comparing the effects of well-watered and water-stressed conditions on three plants: Tidzi, Meiji, and City Hanchan. Under well-watered conditions, attributes like biomass and chlorophyll increase. Under water-stressed conditions, some attributes decrease, such as H₂O₂ and MDA, with other increases like biomass and chlorophyll. Arbuscular Mycorrhizal Fungi (AMF) is indicated as a factor. Green arrows show increases, while red arrows show decreases.